Piperonal chalcone derivative incorporating the pyrazolo[3,4-b]pyridine moiety; crystal structure, spectroscopic characterization and quantum chemical investigations (2023)
A single crystal of a piperonal chalcone derivative was obtained, fully characterized, and crystallized by a slow evaporation technique. The synthesized compound was characterized by UV-Visible, FT-IR, HRMS, 1H NMR, and 13C NMR spectroscopic studies and X-ray crystallography, revealing that the crystal belongs to a triclinic crystal system with a P1̄ space group, Z = 2. In the present work, we focus on molecular modeling studies such as Hirshfeld surface analysis, energy framework calculations, frontier molecular orbital analysis, natural bond orbital analysis, and NLO properties of a π-conjugate system combining the chalcone and the pyrazole[3,4-b]pyridine scaffolds to describe the in-depth structural analysis thereof. Good agreement was found between the calculated results and experimental data. In addition, Hirshfeld surface analysis of the crystal structure showed that the intermolecular stabilization in the crystal packing comes mainly from H⋯H bond interactions. The chalcone crystal exhibits significant NLO properties suggesting that it could be considered a potential candidate for application in nonlinear optical devices.